2013
DOI: 10.1186/2193-1801-2-54
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A stimulates human prostate cancer cell migration via remodelling of calcium signalling

Abstract: Bisphenol A (BPA), the principal constituent of reusable water bottles, metal cans, and plastic food containers, has been shown to be involved in human prostate cancer (PCa) cell proliferation. The aim of the present study was to explore the effect of BPA on PCa cell migration and the pathways involved in these processes. Using the transwell technique, we clearly show for the first time that the pre-treatment of the cells with BPA (1–10 nM) induces human PCa cell migration. Using a calcium imaging technique, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 48 publications
(67 reference statements)
4
64
1
1
Order By: Relevance
“…A recent study showed BPA treatment increased the levels of Orai1 protein, a Ca 2+ selective ion channel, and subsequently stimulate prostate cancer cell migration 163. This finding suggests involvement of BPA in regulating ion channel expression and function, a mechanism through which breast cancer may be initiated or progressed.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study showed BPA treatment increased the levels of Orai1 protein, a Ca 2+ selective ion channel, and subsequently stimulate prostate cancer cell migration 163. This finding suggests involvement of BPA in regulating ion channel expression and function, a mechanism through which breast cancer may be initiated or progressed.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study has reported an increase in Orai1 protein levels induced by low doses of BPA (1-10 nM) in prostate cancer cells, leading to an amplification of the store operated Ca 2+ entry and stimulating cancer cell migration [38]. These results provide novel insights into the molecular mechanisms involved in the effects of an environmental factor on cancer cells.…”
Section: Phosphorylation Of the Ryr Increasesmentioning
confidence: 89%
“…BPA regulates the expression of an important component of SOCE: Orai1 (but not STIM1), and also other channels, such as TRPV6 and Ca 2+ -activated potassium channels BKca and IKca in LNCaP cells. The inhibition of SOCE reduces the migration of androgen-dependent or -independent prostate cells [79].…”
Section: Calcium Channels Migration and Metastasis In Prostate Cancermentioning
confidence: 99%